Pertumbuhan dan Hasil Dua Varietas Jagung Manis terhadap Pemberian Pupuk Hayati pada Lahan Rawa Lebak - Achmadi Achmadi; Mahdiannoor; Nurul Istiqomah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2017)
Lebak wetland is land that has many limiting factors for the development of food crop cultivation, especially maize. These limiting factors include excess water, varied soil fertility and toxic elements. Efforts that can be made to increase corn production are by using the right varieties and providing fertilizers, especially using biological fertilizers. This study aims to determine (i) the effect of two sweet corn varieties on several doses of biological fertilizers, (ii) the influence of varieties, (iii) the effect of doses of biological fertilizers, (iv) the interaction of varieties with biological fertilizers, (v) the best varieties and (vi ) the best dosage of biofertilizer on the growth and yield of two varieties of sweet corn. The study was conducted in Pasar Senin Village, Amuntai Tengah District, Hulu Sungai Utara Regency from April to July 2017. Using a Randomized Block Design (RBD) Factorial 2 factors. The first factor is sweet corn varieties, namely v1 = Bonanza F1 and v2 = Valentino F1. The second factor of the dosage of biological fertilizer is: h0 = 0 kg.ha-1, h1 = 50 kg.ha-1, h2 = 100 kg.ha-1 and h3 = 150 kg.ha-1. The results showed no interaction of varieties with fertilizers on all observation variables, varieties had an effect on plant height, number of leaves, stem diameter, ear weight with straws and without weight, ear length with straws and without cornhusk and diameter with strawberries and without nuts with the best treatment is v1, while biofertilizer influences the weight of the cob with the weight, the length of the cob with the straw and without the weight and diameter of the cob with the kelobot and without the kelob with the best treatment is h2.